2021
DOI: 10.1111/sifp.12157
|View full text |Cite
|
Sign up to set email alerts
|

Does the Belief That Contraceptive Use Causes Infertility Actually Affect Use? Findings from a Social Network Study in Kenya

Abstract: The belief that contraceptive use causes infertility has been documented across sub-Saharan Africa, but its quantitative association with actual contraceptive use has not been examined. We collected and analyzed sociocentric network data covering  percent of the population in two villages in rural Kenya. We asked respondents to nominate people from their village (their network), and then we matched their network (alters) to the individual participant (ego) to understand how their beliefs and behaviors differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 47 publications
0
20
1
1
Order By: Relevance
“…Existing evidence among young people supports that peers influence contraceptive use [33,35] and specifically condom use [42][43][44][45], but given that Kenya's contraceptive method mix among young people includes a range of methods, including implants, injectables and condoms, it is important to better understand if social influences are associated with method use and choice, including commonly used hormonal methods. Access to hormonal methods for young people is beneficial in that hormonal methods can provide longer term protection from pregnancy, are more reliable, may be more cost effective, and are more convenient as compared to coitally-dependent methods such as condoms or emergency contraception; however, barriers to use of hormonal methods are common, including the belief that contraceptives cause infertility as well as fear of real side effects [46]. In this context of high teenage pregnancy and substantial evidence on the role of social influences on contraceptive use among women of reproductive age, it is important to understand the role of social influences on contraceptive method choice among both young women and men.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Existing evidence among young people supports that peers influence contraceptive use [33,35] and specifically condom use [42][43][44][45], but given that Kenya's contraceptive method mix among young people includes a range of methods, including implants, injectables and condoms, it is important to better understand if social influences are associated with method use and choice, including commonly used hormonal methods. Access to hormonal methods for young people is beneficial in that hormonal methods can provide longer term protection from pregnancy, are more reliable, may be more cost effective, and are more convenient as compared to coitally-dependent methods such as condoms or emergency contraception; however, barriers to use of hormonal methods are common, including the belief that contraceptives cause infertility as well as fear of real side effects [46]. In this context of high teenage pregnancy and substantial evidence on the role of social influences on contraceptive use among women of reproductive age, it is important to understand the role of social influences on contraceptive method choice among both young women and men.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Mollborn, Domingue, and Boardman (2014a) determined the U. S. high schools' norm against teen pregnancy based on survey data of the National Longitudinal Study of Adolescent Health and found schools' norms to differ significantly. Sedlander et al (2021) created a more proximal collective norm of contraception use by aggregating participant's chosen social network (up to five people with whom they spend the most time). Such differences in collective norms across schools, communities, or countries reflect important collective-specific attributes that need to be considered in normative influences.…”
Section: Link #3: Aggregation Linkmentioning
confidence: 99%
“…Most of them (18 out of 26, 69.2%) found a negative relationship. Specifically, beliefs in health misinformation were associated with less contraceptive use (DeClerque et al, 1986;James-Hawkins & Broaddus, 2016;Sedlander et al, 2021), less condom use (Kalichman & Simbayi, 2004), and less COVID-19 preventive behaviors (e.g., wash hands, maintain social distance, wear masks) (Allington et al, 2021, study 1, 2 and 3; Barua et al, 2020;Bridgman et al, 2020;Hornik et al, 2021;Romer & Jamieson, 2020;Roozenbeek et al, 2020, study 2, 3 and 5;Sternisko et al, 2021, study 3;Teovanović et al, 2021;X. Wang et al, 2020).…”
Section: Behavioral Impactmentioning
confidence: 99%